Transformação digital e empreendedorismo feminino: Estratégias de sucesso nas redes sociais na cidade de Manaus - Oliveira, Nathalia Grana de (Brasil, 2025)
The research had the general objective of analyzing how women entrepreneurs in Manaus-AM use digital platforms as business marketing strategies. Specifically, identify the digital platforms used by these entrepreneurs, profile them and cite the advantages and disadvantages when using the platforms. With the justification of expanding knowledge about the scenario of women's entrepreneurship in the face of new market practices, especially the use of tools such as digital platforms. The methodology was descriptive, qualitative, an electronic questionnaire was administered to 32 entrepreneurs using Google Forms. The results show that the entrepreneurs are young, aged between 25 and 34 years old, with a good level of education, working in the services and commerce sector, with 1 to 3 years in the market. Digital marketing has proven to be a strategic tool promoting products, building customer loyalty and attracting new consumers, highlighting the use of social networks, especially Instagram, but handling these technologies requires training, being one of the main limitations, thus suggesting future studies that delve deeper into the subject.